The Impact of the Problem-Based Learning Model with a Scientific Approach on Students' Creative Thinking and Design Thinking - Azizah, Lathifatul Muwafiq; Prayogi, Saiful; Gummah, Syifa’ul; Herayanti, Lovy; Habibi, Habibi (Lensa: Jurnal Kependidikan Fisika, 2024)
This study investigates the impact of integrating the scientific approach within the problem-based learning (PBL) model on students' creative thinking and design thinking skills, specifically in the context of physics education. The primary objective is to evaluate whether this combined approach significantly enhances these higher-order thinking skills compared to conventional teaching methods. A quasi-experimental design was employed with non-equivalent control groups, comprising two eighth-grade classes: an experimental group receiving the PBL model with a scientific approach, and a control group taught using traditional methods. Pretests and posttests were administered to assess the students’ creative and design thinking abilities. Data were analyzed using parametric statistical methods, including normality and homogeneity tests, followed by a paired t-test to evaluate the hypothesis. The results indicated that students in the experimental group showed significantly higher improvements in both creative and design thinking skills compared to the control group. Key dimensions such as comfort with uncertainty, attention to process, and confidence in creativity were notably enhanced in the experimental group. The findings suggest that integrating the scientific approach within PBL fosters an engaging and effective learning environment, promoting not only cognitive development but also collaboration, communication, and problem-solving skills. These results have important implications for educational practices, highlighting the value of adopting student-centered learning models to equip students with the critical skills needed for future challenges.